Estudio sobre la negociación y su influencia en las actividades comerciales de la ciudad de Quito. - Vargas Verdugo, Paola Andrea (2014)
He study of negotiation and it's influence in the commercial activities in the city of Quito, is important and transcendental at the entrepreneurial, commercial and professional level of the country. There is a great confusion among most of the entrepreneurs in the city in distinguishing between sales and negotiation, as these are complimentary yet distinct. Negotiation leads to agreements between the parties whereas sales involves commercial activities that provoke the exchange of a product or service. This study is carried out in Quito, as this city is the capital of the country and a place where the most important negotiations occur given the domicile and presence of organizations and decision making entities. Negotiation is a current concern and it is important to appraise the level of its presence, its growth perspective and the technical grade it has developed since this subject has not been formally studied nor has it been approached with responsibility and adequate technique. This investigation attempts to determine the current state of negotiation in the capital of the Ecuadorean nation